East comes West : Asian religions and cultures in North America - Richardson, E. Allen, 1947- (New York : Pilgrim Press, 1985)
Examines four Asian religions --Hinduism, Buddhism, Sikhism, and Islam-- as they are manifest in the United States and Canada
Includes index
Bibliography: p. 195-205
Keywords: Hinduism -- North America; Buddhism -- North America; Sikhism -- North America; Islam -- North America; North America -- Religion